A cross sectional epidemiological survey of shipyard workers exposed to hand-arm vibration. Issue 1 (January 1992) - Letz, R; Cherniack, M G; Gerr, F; Hershman, D; Pace, P
Abstract : The hand-arm vibration syndrome, widely known as vibration white finger, is a disorder of nerves and blood vessels that occurs in workers exposed to segmental vibration. A cross sectional symptom survey was performed on a sample of workers employed by a large shipyard in the north eastern United States. Random samples were drawn from departments composed of full time dedicated pneumatic grinders, workers with part time exposure to vibration, and other workers not exposed to vibratory tools. Of the 375 workers sampled, 79% responded. The prevalence of white finger symptoms was 71%, 33%, and 6% among the three exposure groups respectively. Similarly, the prevalence of numbness and tingling in the hands and fingers in the three exposure groups was 84%, 50%, and 17%. Workers were classified according to the Stockholm Workshop staging systems for vascular and sensorineural symptom severity. Exposure-response analyses of both vascular and sensorineural stage showed monotonically increasing prevalence of higher disease stages with increasing duration of exposure. Logistic regression analysis, performed to control for potential confounding factors including age and current smoking state, produced highly significant (p less than 0.001) associations between cumulative duration of exposure and prevalence of symptoms. In these analyses smoking state was significantly related to vascular and sensorineural symptoms and age was not. Average latency to onset of symptoms was less than five years of full time equivalent work with vibratory tools. Logistic regression analyses were performed to assess the effect of use of particular work practices on reported symptoms. Further study of this workforce with objective, quantitative measures of peripheral neurological and vascular function is required to characterise the clinical and subclinical effects of vibration exposure.